Effects of Halloysite Nanotube Reinforcement in Expandable Graphite Based Intumescent Fire Retardant Coatings Developed Using Hybrid Epoxy Binder System - Gillani, Q.F. (Springer Verlag, 2018)
In this study, the effects of halloysite nanotubes (HNTs) reinforcement in expandable graphite based intumescent fire retardant coatings (IFRCs) developed using a polydimethylsiloxane (PDMS)/phenol BA epoxy system were investigated. Intumescent coating formulations were developed by incorporating different weight percentages of HNTs and PDMS in basic intumescent ingredients (ammonium polyphosphate/melamine/boric acid/expandable graphite, APP/MEL/BA/EG). The performance of intumescent formulations was investigated by furnace fire test, Bunsen burner fire test, field emission electron microscopy (FESEM), thermogravimetric analysis (TGA), transmission electron microscopy (TEM), and Fourier transform infrared analysis (FTIR). The Bunsen burner fire test results indicated that the fire performance of HNTs and PDMS reinforced intumescent formulation has improved due to the development of silicate network over the char residue. Improved expansion in char residue was also noticed in the formulation, SH(3), due to the minimum decomposition of char carbon. FESEM and TEM results validated the development of silicate network over char layer of coating formulations. A considerable mass loss difference was noticed during thermal gravimetric analysis (TGA) of intumescent coating formulations. Reference formulation, SH(0) with no filler, degraded at 300 °C and lost 50 of its total mass but SH(3), due to synergistic effects between PDMS and HNTs, degraded above 400 °C and showed the maximum thermal stability. XRD analysis showed the development of thermally stable compound mulltie, due to the synergism of HNTs and siloxane during intumescent reactions, which enhanced fire performance. FTIR analysis showed the presence of incorporated siloxane and silicates bonds in char residue, which endorsed the toughness of intumescent char layer produced. Moreover, the synergistic effect of HNTs, PDMS, and other basic intumescent ingredients enhanced the polymer cross-linking in binder system and improved fire resistive performance of coatings. © 2018 Chinese Chemical Society, Institute of Chemistry, Chinese Academy of Sciences and Springer-Verlag GmbH Germany, part of Springer Nature